Objections! the ultimate guide to mastering the art and science of getting past no - Blount, Jeb 1966- (Wiley, 2018)
"Following in the footsteps of his blockbuster bestsellers Fanatical Prospecting and Sales EQ, Jeb Blount's Objections is a comprehensive and contemporary guide that engages your heart and mind. In his signature right-to-the-point style, Jeb pulls no punches and slaps you in the face with the cold, hard truth about what's really holding you back from closing sales and reaching your income goals. Then he pulls you in with examples, stories, and lessons that teach powerful human-influence frameworks for getting past NO - even with the most challenging objections"...